Extremities Amputations in King Abdulaziz University Hospital (2005-2009) - Mohammed M. Badri; Wail A. Tashkandi; Saleh M. Aldaqal; Abrar A. Nawawi; Ahmed M. Kensarah; Hasan A. Alzahrani (Journal of King Abdulaziz University: Medical Sciences, 2023)
Diabetic foot disorders are responsible for the majority of limb amputations in Jeddah. They represent at least 50% of causes of lower limb amputations. A retrospective study was designed to identify the pattern of amputations, aetiological factors, and the percentage of diabetic extremities amputations performed at King Abdulaziz University Hospital over five years. The records of 222 patients who had 252 limb amputations were reviewed. The median age of patients reviewed was 63 years. The male to female ratio was 3:1. Foot ulcer was the most common presentation among diabetic who underwent amputation (90%). Lower limb amputations were the most common (96.4%) and more than half of it (55%) was minors. Diabetes mellitus headed the list of indications in lower limb amputations (90%). Most of the amputations were carried out by general surgeons followed by vascular surgeons and orthopedics. Re-amputation was necessary in 24 patients. The mortality rate was (7.2%) and only 8.8 % of the amputees have been rehabilitated post amputations. Accordingly, every effort should be made to avoid amputation in diabetics, particularly with limited resources for rehabilitation in developing countries.